2011
DOI: 10.3892/ijmm.2011.725
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adipose-derived stem cells for peripheral nerve repair

Abstract: Abstract. Mesenchymal stem cells have become a very attractive source of cell implantation for neural tissue engineering. The ideal stem cells for transplantation should be easily obtained, and should rapidly proliferate in vitro and have low immunogenicity. The purpose of this study was to investigate the regenerative potential of adipose-derived stem cells (ADSC) on peripheral nerve repair. ADSCs were isolated from rat adipose tissue and cultured until adherent cells became morphologically homogeneous with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
3
26
2
Order By: Relevance
“…Therefore, the absence of muscle recovery in the MSC treated groups might be justified by an insufficient time to achieve complete muscle reinnervation (24). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the absence of muscle recovery in the MSC treated groups might be justified by an insufficient time to achieve complete muscle reinnervation (24). …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies using MSC-based therapy showed positive effects in the sciatic nerve regeneration 6 to 12 weeks after neurotmesis varying from 3-to-10–mm nerve gap (6, 8, 23, 24, 26, 3840). Our results are in accordance with these findings, indicating that after a neurotmesis of 10 mm, the nerve regeneration is enhanced by MSC transplantation, even in a short period of 35 days.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments also confirmed a benefit of applying the ASCs in promoting nerve regeneration after transplanted into the injured site. Several previous studies have demonstrated the utilization of ASCs improved axonal regeneration in vivo , and this effect has been attributed mainly to the environmental support provided by the ASCs during nerve regeneration44454647.…”
Section: Discussionmentioning
confidence: 96%
“…MSCs have shown promise in improving clinical and electrophysiological outcomes in animal models of peripheral nerve injury (3739). In comparison to local delivery, some groups have demonstrated significantly accelerated functional neuronal recovery following systemic administration of MSCs (40).…”
Section: Mscs Promote Nerve Regenerationmentioning
confidence: 99%